Analoški procesi nastajanja drugotnih vzorcev zlaganja v pozni praslovanščini - Šekli, Matej (Slavistična revija, 2013)
Taking for its basis the critical analysis of (Old) Church Slavic material, the article investigates Late Proto-Slavic word-formational models of compounding, within both the diachronic and the synchronic analytic approach. The synchronic perspective offers an overview of the typology of compounds on the basis of their morphemic structure (morphological point of view) and the word-formational meaning (semantic point of view). In the diachronic part of the discussion the origin of the different models of compounding is attempted,together with the analysis of Late Proto-Slavic models responsible for the creation of secondary compounds, especailly in terms of their analogical word-formational changes.
Keywords: analogija; analogy; besedotvorje; cerkvena slovanščina; Church Slavic; compounds; Old Church Slavic; praslovanščina; Proto-Slavic; stara cerkvena slovanščina; word formation; zloženke